2003
DOI: 10.1364/oe.11.003284
|View full text |Cite
|
Sign up to set email alerts
|

Highly efficient waveguide bends in photonic crystal with a low in-plane index contrast

Abstract: We report on the realization and characterization of highly efficient waveguide bends in photonic crystals made of materials with a low in-plane index contrast. By applying an appropriate bend design photonic crystal bends with a transmission of app. 75 % per bend were fabricated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(5 citation statements)
references
References 11 publications
0
5
0
Order By: Relevance
“…The photonic defect edge modes can still transmit but will have dispersion after bending. In order to reduce the dispersion at the bend and achieve broadband and high efficiency transmission, the structure at the bend of the waveguide should be further optimized [26][27][28][29][30]. Because the topological edge modes have the properties of topological protection, the distribution of |E| does not weaken significantly when it passes through the double 90° bends.…”
Section: Methods Of Constructing Topological Edge Statementioning
confidence: 99%
“…The photonic defect edge modes can still transmit but will have dispersion after bending. In order to reduce the dispersion at the bend and achieve broadband and high efficiency transmission, the structure at the bend of the waveguide should be further optimized [26][27][28][29][30]. Because the topological edge modes have the properties of topological protection, the distribution of |E| does not weaken significantly when it passes through the double 90° bends.…”
Section: Methods Of Constructing Topological Edge Statementioning
confidence: 99%
“…At the same time in a separate work, Kafesaki et al reported that the displacement of corner holes has a positive effect on transmission ratio in 2D triangular PhC with double 60 degree bend [14]. Then Augustin et al fabricated a PhC slabs in 2003 and showed that by adding some extra holes in the double 60 degree bend, transmission efficency can be improved [9]. In 2006, topology optimization method was applied for a 2D PhC waveguide to reduce unwanted reflection from the 90 degree bend to a minimum, using topology optimization [15].…”
Section: Introductionmentioning
confidence: 99%
“…[6][7][8][9][10][11] An efficient PC waveguide can, therefore, be obtained by simply introducing straight or bent line defects to the PC structures, making use of their low radiative loss within their bandgap. [12][13][14][15][16][17] Recent studies on PCs have demonstrated that negative refraction can also be obtained via the high crystal anisotropy of these artificially left-handed structures. [18][19][20][21] Because of their ability to control the propagation of electromagnetic waves and their compatibility with conventional micromachining techniques, PCs are promising candidates to assist the development of integrated photonic circuits and on-chip optical processing.…”
Section: Introductionmentioning
confidence: 99%